Concept Analysis of Educational Counseling and Guidance ofAli Bin Abi Talib’s Perspective - Ahmad Suhaili, Yayat Hidayatullah (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
This study is an attempt to explore the conceptual of counseling and guidance of Ali bin Abi Tholib’s perspective. By employing descriptive and qualitative research method the study found that The concept of Sayyidina Ali Bin Abi Tholib on the Guidance of Learning pivots on the understanding of a counselor and counselee about the duty and the necessity of their own so that in this case revolves around two important themes namely: Characteristics of counselors concerning two things, the first is the feasibility of the properties and the second is the attitude and behavior. The second, Counselee's Self-Knowledge is related to the level of independence of the counselee to find and deal with the problem. The concept of Guidance and Counseling of Non Formal Education in the perspective of Sayyidina Ali Bin Abi Tholib necessitates the existence of three principles, namely the principle of ease of service (تيسير),, enrichment or expansion of insight (توفير) and the cultivation of authority (توقير).